The Influence of Students', Interests and Family Support through Islamic Boarding School Culture on Higher Education Institution Choice - Intan Humairah; Agus Salim Salabi (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
This study aims to analyze the influence of students's interest and family support on the selection of higher education institutions, with pesantren culture ad an intervening variable. This research employs a quantitative approach using the structural equation modeling partial least squares (SEM-PLS) method. The sample consists of 51 twelfth-grade students at MAS AL-Muslimun Lhoksukon, selected through purposive sampling. Data were collected Likert-scale questionnaires and analyzed using SEM-PLS to examine both direct and indirect relationships among variables. The result indicate that students' interests and family support have a positive and significant effect on pesantren culture. However, students' interest, family support, and pesantren culture do not have a significant effect on the selection of higher education institutions. furthermore, pesantren culture is not proven to mediate the relationship bertween students' interest and family support play a more significant role in shaping pesantren culture than in directly influencing higher education choices. therefore, further research is recomended to consider other factors such as economic conditions, acces to information, and career prospects in order to better understand the decision-making process in selecting higher education institutions.